Rationale and design of the Endurant Stent Graft Natural Selection Global Postmarket Registry (ENGAGE): interim analysis at 30 days of the first 180 patients enrolled - Böckler, Dittmar; Fitridge, R.; Wolf, Y.; Hayes, P.; Silveira, P.; Numan, Füruzan; Riambau, V. (The journal of cardiovascular surgery, 2010)
Aim. The Endurant Stent Graft Natural Selection Global Postmarket Registry (ENGAGE) is a long-term 1200-patient multicenter prospective study initiated to augment the knowledge base (poolable and comparable) about endovascular aortic repair (EVAR) in a real-world population implanted with a single latest-generation stent graft system (Endurant). With enrollment ongoing at 80 high-volume sites, the registry has limited inclusion/exclusion criteria or procedural specification. Technical and clinical data will be reported through 5 years.
Gesehen am 17.02.2023